2018
DOI: 10.3892/etm.2018.5718
|View full text |Cite
|
Sign up to set email alerts
|

FPOA induces the apoptosis of HepG2 cells

Abstract: Abstract. The triterpenoid 3-acetoxylanosta-8,24-dien-21-oic acid (FPOA) is isolated from the fruiting body of Fomitopsis pinicola. The present study reports that FPOA exerts cytotoxic activity and describes the molecular mechanism of FPOA-induced apoptosis on human HepG2 hepatoma cells. FPOA exhibited significant cytotoxic effects against HepG2, MCF-7 and HeLa cells. However, FPOA was particularly cytotoxic towards HepG2 cells, with a half maximal inhibitory concentration value of 42.10 µM, thus these cells w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…The results showed that FPOA is a potential anti-cancer agent. (Song et al, 2018) 3.1.4 Migration inhibition and apoptotic effect: Every year, colorectal cancer {CRC} is increasing worldwide. Almost half of the affected patients died by this disease.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that FPOA is a potential anti-cancer agent. (Song et al, 2018) 3.1.4 Migration inhibition and apoptotic effect: Every year, colorectal cancer {CRC} is increasing worldwide. Almost half of the affected patients died by this disease.…”
Section: Introductionmentioning
confidence: 99%